The lighting supervisor's toolkit : collaboration, interrogation, and innovation toward engineering brilliant lighting designs - Weber, Jason E. (The Focal Press toolkit series, 2021)
"The Lighting Supervisor's Toolkit guides readers through the Lighting Supervisor's production process with an emphasis on the importance of the collaborative nature of the role. Lifting the veil on a process regularly learned on the job, this book offers a deeper understanding of the role of Lighting Supervisor and how to take lighting designs from dreams to reality. Readers will learn to communicate with designers, analyze drawings, plan installations, document decisions, supervise crews, and innovate outside-the-box solutions. Providing guidance for technically focused individuals seeking deeper understanding of the profession, The Lighting Supervisor's Toolkit is ideal for students and professional technicians looking to take on important leadership roles in theatrical and entertainment lighting"--